Livestock Farming Adoption in Rural Bangladesh: Determinants and Impacts on Household Income and Women's Dietary Diversity - Toma Deb Nath; Arindam Biswas; Sheikh Faruk Ahmed (Food and Energy Security)
ABSTRACT The crucial role of women in livestock farming is widely recognized, bringing multiple benefits such as increased household income, fostering stability, and improved nutrition security for women. Thus, the current study investigated the determinants and impacts of livestock farming adoption on household income and women's dietary diversity. To achieve the objectives, a survey was conducted among 367 women farmers residing in four villages located in the Mymensingh district of Bangladesh. Both the double hurdle model and the Tobit econometric model were employed to determine the determinants of livestock farming adoption. To evaluate the impact of adopting livestock farming, the study utilized three treatment effect estimators: regression adjustment, inverse probability weighting, and inverse probability weighting regression adjustment. The findings revealed that factors including education, family labor, training experience, credit access, extension contacts, distance from the extension office, and mobile ownership had a significant influence on the adoption of livestock farming. The treatment effect model showed that women who had adopted livestock farming had higher household income, ranging from 88.38% to 94.55%, as well as a higher level of dietary diversity, ranging from 56.03% to 66.38%, compared to non‐adopters. Therefore, in order to promote the growth of livestock farming in the study area, governmental and non‐governmental organizations should reinforce their efforts by emphasizing the determinants influencing the adoption process. Moreover, to inspire women and drive higher adoption rates in livestock farming, the provision of readily available and accessible motivational training and extension services should be enhanced.